LEGAL REGULATION OF CREATING AND USING DEEPFAKES - ARKHIEREEV Nikolay Viktorovich (Правовое государство: теория и практика)
With the development of artificial intelligence, there are more and more technologies developed on its basis, including deepfake technology, which allows to create and modify audiovisual digital content in order to create the most realistic and believable images that are not true and do not exist in reality. Meanwhile, the purpose for which a deepfake is created may be legitimate or illegitimate. In any case, however, deepfakes undermine trust in information, since the likelihood that the image one sees on a device screen exists only in the electronic world increases exponentially. Purpose: to analyze the legal regulation of creating and using deepfakes, identify gaps, and find ways to make deepfakes safe. Methods: empirical methods of comparison, description, interpretation; theoretical methods of formal and dialectical logic; specific scientific methods: legal-dogmatic and interpretation of legal norms. Results: the article formulates proposals, the implementation of which will make it possible to exclude violations of the rights and legitimate interests of citizens when using deepfakes.